Defect‐Free Alternating Conjugated Polymers Enabled by Room‐ Temperature Stille Polymerization. Issue 16 (23rd February 2022) - Ma, Bowei; Shi, Qinqin; Ma, Xiaoying; Li, Yawen; Chen, Hao; Wen, Kaikai; Zhao, Ruihua; Zhang, Fengjiao; Lin, Yuze; Wang, Zhixiang; Huang, Hui
Abstract: The Stille cross‐coupling polymerization is one of the most efficient synthetic methods for donor–acceptor (D–A) type π‐conjugated polymers (CPs). Nevertheless, thermal‐activation Stille polymerization readily produced homocoupling defects, resulting in batch‐to‐batch variations in copolymers quality and deteriorating the device performance of electronics and optoelectronics. Here, a room‐temperature Stille‐type polymerization was developed, the utility and generality of which were demonstrated by synthesis of twelve D–A CPs with high molecular weights. Importantly, the resultant copolymers possessed no homocoupling (hc) structural defects, while hc reactions were observed in the thermal‐activation Stille reactions. Thus, the organic field‐effect transistors (OFETs) based on the former exhibited twofold higher charge transport mobility (2.10 cm 2 V −1 s −1 ), since it possessed stronger crystallinity and lower trap density of states (tDOS). Abstract : The synthesis of conjugated polymers (CPs) often suffers from high temperature and indistinct homocoupling structural defects. In this study, the first room‐temperature Stille cross‐coupling polymerization was explored. Surprisingly, this method produced defect‐free CPs, which enhanced their charge transport properties. Therefore, this work paves the road for the development of plastic electronics and optoelectronics.